2016
DOI: 10.1016/j.ibmb.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Calcium influx enhances neuropeptide activation of ecdysteroid hormone production by mosquito ovaries

Abstract: A critical step in mosquito reproduction is the ingestion of a blood meal from a vertebrate host. In mosquitoes like Aedes aegypti, blood feeding stimulates the release of ovary ecdysteroidogenic hormone (OEH) and insulin-like peptide 3 (ILP3). This induces the ovaries to produce ecdysteroid hormone (ECD), which then drives egg maturation. In many immature insects, prothoracicotropic hormone (PTTH) stimulates the prothoracic glands to produce ECD that directs molting and metamorphosis. The receptors for OEH, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…Total ecdysteroids secreted by ovaries were quantified using an enzyme-linked immunosorbent assay (EIA) [ 10 ]. Ovaries were dissected from females 20 h after feeding, which corresponds with when ecdysteroid production peaks in ovaries after consumption of rat blood [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total ecdysteroids secreted by ovaries were quantified using an enzyme-linked immunosorbent assay (EIA) [ 10 ]. Ovaries were dissected from females 20 h after feeding, which corresponds with when ecdysteroid production peaks in ovaries after consumption of rat blood [ 8 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ovaries were dissected from females 20 h after feeding, which corresponds with when ecdysteroid production peaks in ovaries after consumption of rat blood [ 8 ]. The ovaries from two females were pooled and incubated together in 60 µl Beyenbach’s saline [ 10 ] on a shaker for 6 h at 27 °C and ~90% RH. Following this incubation period, medium supernatant containing secreted ecdysteroids was collected and frozen at – 20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The previous in-house effort to synthesize AaILP3 was long and complicated but finally successful (Brown et al, 2008) and enabled the elucidation of its binding to the insulin receptor and diverse functions in Ae. aegypti (Wen et al, 2010; Gulia-Nuss et al, 2011; Castillo et al, 2011; Gulia-Nuss et al, 2012; Gulia-Nuss et al, 2015; McKinney et al, 2016). Fortunately, commercial peptide synthesis has advanced greatly and synthesis of AsILP3 and AsILP4 in milligram quantities was a reasonable expense, given the bioactivity and stability of the product.…”
Section: Discussionmentioning
confidence: 99%
“…A similar system has also been observed in the mosquito Aedes aegypti . 78 These authors reported that Ca 2+ -influx enhances neuropeptide activation of ecdysteroids hormone production by mosquito ovaries.…”
Section: Gross Mechanisms For Coping With Excess Ca 2+ mentioning
confidence: 99%